Digital Prophetic Leadership: Navigating Hybrid Learning Ecosystems in Islamic International Schools - Nuruz Zainia; Abdur Rosi; Hafidzi Hafidzi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This research explores the conceptualization and implementation of "Digital Prophetic Leadership" (DPL) within Islamic International Schools navigating hybrid learning ecosystems. It addresses the tension between rapid digital transformation and the preservation of spiritual-moral values. This study employs a qualitative case study design with a constructivist paradigm. Data were gathered through semi-structured interviews with school leaders, digital ethnography (netnography) within Learning Management Systems, and document analysis of school policies. Thematic analysis was used to interpret the data. The results reveal that DPL manifests through four prophetic pillars: Siddiq (virtual integrity and data transparency), Amanah (stewardship of digital well-being), Tabligh (omnichannel advocacy of values), and Fathanah (technological wisdom and strategic agility). The framework facilitates a "Triadic Alignment" between technology, theology, and teleology, enabling schools to remain digitally agile yet spiritually anchored. This study fills a research gap by synthesizing Western digital leadership constructs with Islamic prophetic traits, offering a roadmap for "sanctifying" digital spaces rather than merely adopting technology.